Diverses fonctions discursives d’une phrase averbale en japonais formée par la séquence - Makoto Kaneko (Discours)
This study aims at examining various discourse functions of the Japanese averbal sentence formed by the sequence . Previous studies have characterized this construction in terms of three aspects : i) expression of a directly perceived event as forming a semantic unit with no distinction between subject and predicate ; ii) anchoring of the event in the moment of perception ; iii) introduction of a new utterance level. From this perspective, the Japanese averbal sentence has been compared with a type of averbal sentence in French, like “Le lavabo qui déborde !”. On the other hand, based on examples taken from newspapers, and former works about averbal sentences in other languages, this study claims that, besides the first type extensively discussed, other three types should be distinguished : i) one which expresses a situation as forming a semantic unit and introduces a displaced utterance level, but with no anchoring in the utterance moment. This type establishes various discourse relations, like Background, Elaboration, Contrast with surrounding sentences ; ii) one which introduces a new utterance level, but does not focus on any unitary event, but to make a prominent topic or a spatial or temporal frame of the referent of the noun phrase ; iii) one which shares no characteristics of the first type and is specialized in focusing on a discourse topic whose scope amounts to the whole text.